Uterine tumor resembling ovarian sex-cord tumor (UTROSCT) with sarcomatous features without recurrence after extended radical surgery: A case report. Issue 11 (March 2020) - Sato, Miho; Yano, Mitsutake; Sato, Shimpei; Aoyagi, Yoko; Aso, Saki; Matsumoto, Harunobu; Yamamoto, Ichiro; Nasu, Kaei
Abstract: Rationale: The malignant potential and the appropriate treatment of uterine tumor resembling ovarian sex-cord tumor (UTROSCT) is controversial. Although these tumors generally have benign outcomes, several reports have described recurrences, metastases, and deaths associated with this disease. Patient concerns: A 57-year-old Japanese woman (gravida 2, para 2) was referred to our hospital for the evaluation and treatment of uterine fibroids. Magnetic resonance imaging revealed a right ovarian mass and multiple fibroids in the uterine myometrium. Diagnoses: The patient was diagnosed with UTROSCT with sarcomatous features. Interventions: She initially underwent a total abdominal hysterectomy and bilateral salpingo-oophorectomy, followed by second-stage surgery comprising pelvic and para-aortic lymphadenectomy and subtotal omentectomy. Outcomes: No postoperative recurrence was observed in the patient in 36 months. Lessons: In this case, extended radical surgery prevented the development of recurrent disease in a patient with UTROSCT with sarcomatous features. These clinicopathological findings suggest that UTROSCT is associated with several risk factors, including older age, presence of necrosis, lymphovascular invasion, significant nuclear atypia, and significant mitotic activity. This lesion type should be considered malignant and treated with curative intent.